Additional data about fauna and distribution of the subgenus Furcilethrus Nikolajev, 1968, the genus Lethrus Scopoli, 1777 (Coleoptera: Geotrupidae: Lethrinae) - G.V. Nikolajev; Ye.S. Ivanova (Кавказский энтомологический бюллетень, 2014)
Review of the subgenus Furcilethrus Nikolajev, 1968 of the genus Lethrus Scopoli, 1777 is given. Two new species are described from mountains of Tajikistan: L. muskinabadensis Nikolajev et Ivanova, sp. n. from southern slopes of Karategin Range and L. rustam Nikolajev et Ivanova, sp. n. from western part of Vakhsh Range. The fisrt new species is close to L. michailovi Nikolajev et Schukronajev, 1977 known from northern slopes of Surkhku Range; the second new species is close to L. sohrab Nikolajev, 1976 also known from Surkhku Range. Lectotype of L. furcatus Jakovlev, 1890 (deposited in Zoological Institute of Russian Academy of Sciences, Saint Petersburg) is designated. New synonymy is established: L. tenuidens Reitter, 1890 = L. staudingeri Reitter, 1893, syn. n. Lethrus obsoletus Semenov, 1894 is considered as subspecies of L. tenuidens Reitter, 1890: Lethrus tenuidens obsoletus Semenov, stat. n. Distribution of all known species of the subgenus Furcilethrusis detailed. Key to species of the genus on males is given.